STUDY A STRUCTURAL BEHAVIOR OF ECCENTRICALLY LOADED GFRP REINFORCED COLUMNS MADE OF GEOPOLYMER CONCRETE - Nhabih, Hussein Talab; Hussein, Ahmed M.; Salman, Marwa Marza (Civil Engineering Journal, 2020)
This study investigated a modern composite material, which is a short geopolymer concrete column (GPCC) reinforced by GFRP bars. The structural performances of GPCC subjected to eccentric load were studied and compared to the normal strength concrete column (NSCC) reinforced by steel bars. In this study, the primary experimental parameters were the reinforcement bars types, load eccentricity, and concrete types. Seven short columns were tested: three normal strength concrete columns reinforced by steel bars, three geopolymer concrete columns reinforced by GFRP bars and one normal strength concrete column without reinforcement. The model dimensions chosen in the present study was a square section of 130×130 mm and a total height of 850 mm. It was shown that the steel bars contribute about 16.47% of column capacity under concentric load. Comparing with the normal strength concrete column, a geopolymer concrete column reinforced by GFRP bars showed a little increase in ultimate load (5.17%) under concentric load. Under the load eccentricity of 130 mm, a geopolymer concrete column reinforced by GFRP bars showed a significant increase in the ultimate load (69.37%). Under large eccentricity, a geopolymer concrete column reinforced by GFRP bars has an outstanding effect on the columns' ultimate load capacity. Also, the sine form can be utilized for GPCC to find the lateral deflection along with the column high at different load values up to the failure.